Angiolymphoid hyperplasia with eosinophilia: Atypical appeareance in an older patient - Karabudak Ozlem; Taskapan Oktay; Bozdogan Onder; Dogan Bilal (Wolters Kluwer Medknow Publications, 2008)
We describe a 76-year-old man presenting with a chronic, non-healing ulcer of six-year duration on his left zygomatic area. The skin biopsy specimen taken from the lesion, showed increased vascular proliferation, edematous endothelial cells in the dermal blood vessels and perivascular eosinophilic/lymphocytic infiltration. The routine and specific blood tests were unremarkable. On the basis of these features, the patient was diagnosed as having angiolymphoid hyperplasia with eosinophilia (ALHE). We present the case because of its rarity in older people, atypical clinical appearance; and stress the consideration of ALHE in the differential diagnosis of chronic non-healing superficial ulcers confined to face and neck.